The role of parent-initiated motivational climate in the development of overtraining syndrome in adolescent elite athletes: a review study - Frydrychová, Z.; Bartošová, K.; Hutecková, S. (Studia Sportiva, 2017)
Parents are not only gatekeepers to sport, they have significant influence on how young athlete perceives and interprets the sport experience. Their influence is mediated through the parent-initiated motivational climate and is not limited to sport environment, but also to non-sport environment. The quality of parent-child relationship is considered to be a predictor of motivation, level of perceived stress and enjoyment of activities in young athlete. It is supposed overtraining as a multifactorial in nature and that non-sport stress may be a contributing factor. The main purpose of this study is to review empirical research works examining the parent-initiated motivational climate in the context of youth elite sport and its potential influence on young elite athlete. Moreover, the study provides theoretical background of the parent-initiated motivational climate in the context of sport participation. This study reviewed empirical research works of quantitative and qualitative research design. From all searched works from 1992 to 2016, fourteen studies fulfilled set requirements. Two qualitative studies focusing on the parent-initiated motivational climate and its relation to overtraining were found out. These studies supported the assumption that non-sport stress contribute in the development of overtraining. Even though no research studies with quantitative research design examining this relationship were found out, they supported the relationship between parent-initiated motivational climate and psychological outcomes associated with sport participation, such as maladaptive behavioural patterns, that are considered to be risks factors to overtraining.